Redistribution through Income Taxation and Public Utility Pricing in the Presence of Energy Efficiency Considerations - Fabian Feger; Doina Radulescu (Center for Economic Studies and ifo Institute (CESifo), 2018)
Many OECD countries such as the USA, the UK or Switzerland are concerned with the affordability of utility services and the distributional consequences inherent in the pricing strategy of basic goods and services, such as electricity. However, the effectiveness of the electricity tariff as a redistribution device is questionable in the presence of a progressive income tax schedule. To shed light on this controversy, we structurally estimate a model that combines public utility pricing and income taxation. We employ a large panel data set on about 105,000 households in the Swiss Canton of Bern from 2008 to 2013, including detailed energy consumption and household income and tax payment characteristics. While the theoretical model predicts that electricity prices should be subsidised in the presence of purely income redistribution concerns, we find a positive mark-up of 49%, in our data. This suggests that, in practice, the government is concerned with energy conservation as well as income redistribution.
Keywords: D12; D31; H21; H23; H24; L94; L98; 330; redistribution; public utility pricing; energy; asymmetric information